Promoters of ASCL1‐ and NEUROD1‐dependent genes are specific targets of lurbinectedin in SCLC cells - Federico Costanzo; Marta Martínez Diez; Gema Santamaría Nuñez; Juan Ignacio Díaz‐Hernandéz; Carlos Mario Genes Robles; Javier Díez Pérez; Emmanuel Compe; Romeo Ricci; Tsai‐Kun Li; Frédéric Coin; Juan Fernando Martínez Leal; Eva Maria Garrido‐Martin; et al. (EMBO Molecular Medicine)
Abstract Small‐Cell Lung Cancer (SCLC) is an aggressive neuroendocrine malignancy with a poor prognosis. Here, we focus on the neuroendocrine SCLC subtypes, SCLC‐A and SCLC‐N, whose transcription addiction was driven by ASCL1 and NEUROD1 transcription factors which target E‐box motifs to activate up to 40% of total genes, the promoters of which are maintained in a steadily open chromatin environment according to ATAC and H3K27Ac signatures. This leverage is used by the marine agent lurbinectedin, which preferentially targets the CpG islands located downstream of the transcription start site, thus arresting elongating RNAPII and promoting its degradation. This abrogates the expression of ASCL1 and NEUROD1 and of their dependent genes, such as BCL2, INSM1, MYC, and AURKA, which are responsible for relevant SCLC tumorigenic properties such as inhibition of apoptosis and cell survival, as well as for a part of its neuroendocrine features. In summary, we show how the transcription addiction of these cells becomes their Achilles’s heel, and how this is effectively exploited by lurbinectedin as a novel SCLC therapeutic endeavor.